Figures of Classic Kamasan Painting as Inspiration for the Creation of Modern Painting - Neode, Haris Candra; Tjokropramono, I Gede Yosef; Budiarta, I Dewa Putu Gede (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
The classic painting of Wayang Kamasan began when the Modara puppet painting, made by I Gede Mersadi was favored by the king of Klungkung. Then he was given the nickname Modara according to the puppet figure he painted. By king Klungkung Modara was sent to work on many projects so that his puppet painting style spread and until now it is known as Classical Painting Wayang Kamasan. The characteristic of this painting can be seen from the coloring technique that uses the sigar warna and sigar mangsi techniques. (Ni Wayan Sri Wedari, 2022:9). Broadly speaking, the forms of wayang can be distinguished through the shape of the face, body shape or abdomen and coils as well as detailed parts of the eyes, eyebrows, nose, mouth, mustache, and other detailed shapes. (I Made Yasana, Menggambar Wayang Klasik Bali 1). Gede Modara who created the Kamasan Wayang style inspired the author to create puppets with a new style through the figures in the Kamasan Classical Puppet. This creation process aims to preserve the Kamasan Classical Puppet and develop it into a modern painting without eliminating the existing packages. The paintings created are expected to be able to become the characteristics of the author.